Innovations in Immunosuppression for Intestinal Transplantation - Dogra, Harween; Hind, Jonathan (Frontiers in Nutrition, 2022)
It has been 57 years since the first intestinal transplant. An increased incidence of graft rejection has been described compared to other solid organ transplants due to high immunogenicity of the bowel, likely because of the need to balance tolerance of dietary antigen with defence against pathogens. Expanding clinical experience, knowledge of gastrointestinal physiology and immunology have progressed immunosuppressive drug regimens. Current regimes try to find the window between prevention of rejection and the risk of infection (the leading cause of death) and malignancy. The ultimate aim is to achieve graft tolerance. In this review we discuss advances in mucosal immunology and technologies informing the development of new anti-rejection strategies with the hope of improved survival in the next generation of transplant recipients.